Chemical composition of the Satureja brevicalyx Epling - Andamayo Flores, Diana Esmeralda (2020)
Introduction: Epling brevicalyx savory grows in the southern Andes of Peru (Ayacucho, Apurimac, Cuzco and Puno), between altitudes of 3300-3800 m, within the chemical composition of the essential oil of Satureja brevicalyx can ﬁnd several constituents as mentonas, pulegonas, linalool. Traditionally it has been used as a digestive, against gastritis, ﬂatulence and antispasmodic.Objective: To identify the chemical composition of the ethanol extract, hexane / ethanol and the aqueous brevicalyx Satureja Epling for secondary metabolites that are of interest in biological therapeutics.M e t h o d s :  T h e  l e a v e s  w e r e  e x u d e d  a n d dehydrated at room temperature, obtaining a greenish dry powder which underwent successive extractions with solvents of increasing polarity. To the obtained extracts phytochemicals identiﬁcation assays.R e s u l t s :  T h e  p h y t o c h e m i c a l  s c r e e n i n g , conducted at the ethanolic extracts, hexane / aqueous ethanol and the leaves, showed the existence  of  several  families  of  secondary metabolites  of  biological  and  pharmacological interest, among which stand out for their signiﬁcant presence of quinones, ﬂavonoids, alkaloids, phenols, tannins.Conclusions: According  to  the  presence  of secondary metabolites in the leaves of Satureja brevicalyx Epling and pharmacological effects reported for the essential oil of the species, it would be important to conduct further studies to serve as evidence to support its traditional use taking into account the efﬁcacy and safety of this plant.